1978
DOI: 10.1001/archderm.114.8.1193
|View full text |Cite
|
Sign up to set email alerts
|

Hydroa vacciniforme

Abstract: Two patients with hydroa vacciniforme, a rare photodermatosis of unknown etiology, demonstrated distinctive scarring and vesiculobullous skin lesions on light-exposed body areas. Results of blood and urine porphyrin studies were normal, and no systemic abnormalities were noted. A small bullous lesion was produced in normal skin in case 1 with 15 times the minimal erythema dose of ultraviolet energy. The conditions of both patients improved while they were taking beta carotene orally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, Bickers et al (1978) reported successful reproduction of the skin lesions in hydroa vacciniforme with large dose (t5 MED) of UV-B within 24 h. The intensive irradiations of UV-B followed by the careful observation ofthe test sites may be a necessary step for the differential diagnosis of actinic prurigo and hydroa vacciniforme.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Bickers et al (1978) reported successful reproduction of the skin lesions in hydroa vacciniforme with large dose (t5 MED) of UV-B within 24 h. The intensive irradiations of UV-B followed by the careful observation ofthe test sites may be a necessary step for the differential diagnosis of actinic prurigo and hydroa vacciniforme.…”
Section: Discussionmentioning
confidence: 99%